2020
DOI: 10.1038/s41598-020-70117-8
|View full text |Cite
|
Sign up to set email alerts
|

An early Pangaean vicariance model for synapsid evolution

Abstract: Genetic isolation due to geographic separation (vicariance) is the best understood cause of vertebrate speciation. nevertheless, it has never been demonstrated in the fossil record across a wide range of taxa. Here, by reviewing in-depth the available data of the Late Palaeozoic (~ 350-250 million years ago), i reconstructed an early pangaean junction-disjunction palaeogeographic model and showed that it coincides strongly with time-calibrated cladograms of the Late palaeozoic synapsids (the primitive ancestor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 86 publications
0
5
0
Order By: Relevance
“…Such a recent resemblance in the molluscan assemblages on either side of the isthmus cannot easily be explained if the final emergence of the isthmus occurred at 3 Ma. Likewise, the occurrence of the atlantiphile tonnoidean gastropod species Linatella caudata in the earlyto-mid Pleistocene Armuelles Formation [103] in Pacific Panama indicate the existence of shallow-water interoceanic exchange [96] between the Pacific and the Caribbean during the whole Early Pleistocene [94,101]. Continued Early or Middle Pleistocene connections are also demonstrated by (now Atlantic) in the Armuelles Formation of Pacific Panama [104].…”
Section: S a M P L E C O P Y U N P U B L I S H E D P A P E Rmentioning
confidence: 82%
See 2 more Smart Citations
“…Such a recent resemblance in the molluscan assemblages on either side of the isthmus cannot easily be explained if the final emergence of the isthmus occurred at 3 Ma. Likewise, the occurrence of the atlantiphile tonnoidean gastropod species Linatella caudata in the earlyto-mid Pleistocene Armuelles Formation [103] in Pacific Panama indicate the existence of shallow-water interoceanic exchange [96] between the Pacific and the Caribbean during the whole Early Pleistocene [94,101]. Continued Early or Middle Pleistocene connections are also demonstrated by (now Atlantic) in the Armuelles Formation of Pacific Panama [104].…”
Section: S a M P L E C O P Y U N P U B L I S H E D P A P E Rmentioning
confidence: 82%
“…Most of the relevant species are marine species for which, if a long-distance dispersal and/or a "sweepstake" dispersal is excluded, there is no way of dispersal to either side of the isthmus other than an exposed transisthmian seaway. The above two biogeographical concepts are used frequently to support phylogeographical conclusions, adding "noise" to the biogeographical signal; however, they might be the result of poorly understood palaeogeographic evolution and/or inaccurate dates for clade divergences due to incorrectly calibrated molecular clocks [94]. This is probably also the case in the biogeography of the Isthmus of Panama, where molecular divergence dates earlier than the "benchmark" date of 3 Ma have been easily attributed to "sweepstake" dispersals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, we note a recent analysis of the distribution of fossil taxa and their palaeoclimate that supports the conclusion that vertebrates did not cross the relatively narrow Palaeozoic marine Ural Seaway (between Siberia and Baltica) via random or ‘sweepstakes’ dispersal. Brikiatis ( 2020 ) investigated the impact of arido-eustatic cycles on the Palaeozoic evolution of vertebrates and copepods and constructed a vicariance model that was highly predictive of fossil distributions and in agreement with sea level stands and paleoclimatic records. He concluded that vicariance, i.e., in situ evolution, was the predominant mode of vertebrate evolution (also supported by recent, more accurate radioisotopic dating of fossiliferous rock containing early synapsid taxa).…”
Section: Vicariance and Dispersal In A Changed Evolutionary Landscapementioning
confidence: 99%
“…62 ). Terrestrial migrations across an isthmus provide evidence that the isthmus was exposed as a land bridge at the time of the migration, whereas the presence of related marine biota on both sides of an isthmus suggests the former presence of a seaway through the isthmus 131 . Evidence from terrestrial biota for the formation of the Isthmus of Panama 1-0.89 Mya has been reviewed under the concept of the Great American Biotic Interchange 17 and, more speci cally, the third terrestrial migration event (GABI 3).…”
Section: Biostratigraphic Datamentioning
confidence: 99%